Integrative analysis of metabolome, proteome, and transcriptome for identifying genes influencing total lignin content in Populus trichocarpa - Zhao, Jia; Chao, Kairui; Wang, Achuan (Frontiers in Plant Science, 2023)
Lignin, a component of plant cell walls, possesses significant research potential as a renewable energy source to replace carbon-based products and as a notable pollutant in papermaking processes. Despite the elucidation of the monolignol biosynthetic pathway, not all monolignol genes influence the total lignin content. ItThe monolignol biosynthetic pathway has been elucidated and it is known that not all monolignol genes influence the total lignin content. However, it remains unclear which monolignol genes are more closely related to the total lignin content and which potential genes influence the total lignin content. In this study, we present a combination of t-test, differential gene expression analysis, correlation analysis, and weighted gene co-expression network analysis to identify genes that regulate the total lignin content onby utilizing multi-omics data from transgenic knockdowns of the monolignol genes, which that includes data related to the transcriptome, proteome, and total lignin content. Firstly, it was discovered that enzymes from the PtrPAL, Ptr4CL, PtrC3H, and PtrC4H gene families are more strongly correlated with the total lignin content. Additionally, the co-downregulation of three genes, PtrC3H3, PtrC4H1, and PtrC4H2, had the greatest impact on the total lignin content. Secondly, GO and KEGG analysis of lignin-related modules revealed that the total lignin content is not only influenced by monolignol genes, but also closely related to genes involved in the "glutathione metabolic process", "cellular modified amino acid metabolic process" and "carbohydrate catabolic process" pathwaypathways. Finally, the it was found that cinnamyl alcohol dehydrogenase genes CAD1, CADL3, and CADL8 emerged as potential contributors to total lignin content. The genes HYR1 (UDP-glycosyltransferase superfamily protein) and UGT71B1 (UDP-glucosyltransferase), exhibiting a close relationship with coumarin, have the potential to influence total lignin content by regulating coumarin metabolism. Additionally, the monolignol genes PtrC3H3, PtrC4H1, and PtrC4H2, which belong to the cytochrome P450 genes, may have a significant impact on the total lignin content. Overall, this study establishes connections between gene expression levels and total lignin content, effectively identifying genes that have a significant impact on total lignin content. It offers and offering novel perspectives for future lignin research endeavours.